1992
DOI: 10.1037/0096-3445.121.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for temporal overlap among contingent mental processes.

Abstract: A series of studies assessed perceptual-motor transmission of stimulus information by measuring lateralization of movement-related brain potentials in a choice reaction task with no-go trials. When stimuli varied in shape and size, lateralized potentials on no-go trials suggested that easily recognized shape information was used to initiate motor preparation and that this preparation was aborted when size analysis signified that the response should be withheld. This indicates that movement preparation can begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
303
4
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(342 citation statements)
references
References 48 publications
26
303
4
9
Order By: Relevance
“…This finding agrees with results of several other studies that have reported small LRPs in go/no-go tasks (e.g. Ilan and Miller, 1999;Miller and Hackley, 1992;Osman et al, 1989). Brain potential evidence also suggests cortical involvement in no-go processing; evidence that would implicate the central mechanism.…”
Section: Incorporating No-go Trialssupporting
confidence: 83%
“…This finding agrees with results of several other studies that have reported small LRPs in go/no-go tasks (e.g. Ilan and Miller, 1999;Miller and Hackley, 1992;Osman et al, 1989). Brain potential evidence also suggests cortical involvement in no-go processing; evidence that would implicate the central mechanism.…”
Section: Incorporating No-go Trialssupporting
confidence: 83%
“…The LRP data showed that participants began to prepare responses based on the easy dimension (location), and that they terminated the preparation at different times, depending on when information from the form dimension became available, indicating that both stimulus attributes were processed simultaneously rather than in a serial manner. Another important complement of our study assessed perceptual-motor transmission of stimulus information in a choice reaction task with no-go trials (Miller & Hackley, 1992). When stimuli varied in shape and size, LRPs in no-go trials suggested that easily recognized shape information initiated response preparation and that this preparation was aborted when size analysis signified that the response should be withheld, contrary to assumptions of discrete models of perceptual-motor information transmission.…”
mentioning
confidence: 86%
“…In the present study, we focused on the assessment of the N2c and P3a components of the ERP in the no-go trials, but we also measured the SN, P3b, and P2a. Earlier scientific studies that explored the nature of this transmission of information were mainly based on the LRP (Miller & Hackley, 1992;Osman et al, 1992). Future studies should pursue an integrative approach in which the N2c, P3a, SN, P3b, P2a, and the LRP are considered simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This arrangement, in turn, depends on the specific details of an experiment, e.g. the task (Meyer et al, 1985), the stimuli (Miller and Hackley, 1992), and subjects' strategies (Smid et al, 1995). In the present case, we saw how a mapping manipulation, though it barely affected RT, could shift processes between the two LRP intervals.…”
Section: Implications For Lrp Fractionation Of Rtmentioning
confidence: 53%